Canada Goose Management Series: Repellents - Drake, David (Rutgers New Jersey Agricultural Experiment Station, Rutgers Cooperative Extension, 2004)
There is a wide range of non-lethal and lethal options available for Canada goose ( Branta canadensis ) management. This fact sheet, part of a series that examines goose management options currently employed, will present information on repellents that may deter geese from visiting your property. We define the technique and explore the advantages and disadvantages of repellents in terms of, among other factors, amount of effort required to implement, effectiveness, and cost. Fact Sheet FS1031 Purpose: To provide information about managing Canadian geese by repellents